A Human Right Can Be in Conflict with one or Several Other Human Rights. / Un derecho humano puede estar en conflicto con uno o varios otros derechos humanos - Petrovska, Iryna I.; Rozvadovsky, Volodymyr I.; Ptashnyk, Iryna R.; Grytsan, Olga A. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The main purpose of the work is to analyze the conflicts between the rights of one person with other rights. To achieve the goal, the authors studied the prevailing norms in the legal field using the comparison method. International and regional legal documents that guarantee the right to life are characterized. It was established that the right to health care occupies a special place. It is determined that in the general complex of rights, women's rights are an integral part of it. Since almost every country does not comply with international standards related to the health of women, which leads to an increased mortality rate.RESUMEN El propósito principal del trabajo es analizar los conflictos entre los derechos de una persona con otros derechos. Para lograr el objetivo, los autores estudiaron las normas vigentes en el campo legal utilizando el método de comparación. Se caracterizan los documentos jurídicos internacionales y regionales que garantizan el derecho a la vida. Se estableció que el derecho a la atención de la salud ocupa un lugar especial. Se determina que, en el conjunto general de derechos, los derechos de la mujer son parte integrante del mismo. Dado que casi todos los países no cumplen con las normas internacionales relativas a la salud de las mujeres, esto lleva a un aumento de la tasa de mortalidad.